The Ecological Sustainability of The Earth System: Classical and Contemporary Interpretation of Surah Ar-Rum (Chapter 30), Verse 41 - Agus Firmansyah; Yumidiana Tya Nugraheni; Margono Wisanto; Siti Wulan Asih (Amorti: Jurnal Studi Islam Interdisipliner, 2023)
The environmental crisis is a problem of human sustainability. Human life cannot be separated from religious teachings that govern divinity, humanity, and the environment. Some religions teach the value of living in harmony with nature. In Islam, there are also several verses that talk about the preservation of nature. Besides that, there are verses explaining the causes of natural damage. This research is library research. The research aims to find out the comparative interpretation of Q.S. Rum verse 41 and the context of Q.S. Rum verse 41. The results of the study are as follows: First, humans are the main actors in environmental damage, both on land and in the sea. Second, humans are able to destroy nature individually and collectively. Collaborative destruction is carried out by making systems and laws that do not care about the preservation of nature.